2020
DOI: 10.7150/thno.49731
|View full text |Cite
|
Sign up to set email alerts
|

Broaden sources and reduce expenditure: Tumor-specific transformable oxidative stress nanoamplifier enabling economized photodynamic therapy for reinforced oxidation therapy

Abstract: Cancer cells immersed in inherent oxidative stress are more vulnerable to exogenous oxidative damages than normal cells. Reactive oxygen species (ROS)-mediated oxidation therapy preferentially aggravating tumor oxidative stress to disrupt redox homeostasis, has emerged as an effective and specific anticancer treatment. Herein, following an ingenious strategy of “broaden sources and reduce expenditure”, we designed a versatile tumor-specific oxidative stress nanoamplifier enabling economized photodynamic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Generally, light source, PSs and O 2 are the three necessary components of PDT. With the continuous development of PSs and optical fiber-guided laser transmission systems, PDT has evolved from theoretical research to clinical research and expanded to imaging and treatment of various cancer and non-cancer diseases 11 - 15 . However, like other therapies, the breadth and depth of PDT's efficacy have not been fully realized due to the limitations such as light penetration depth, inefficient PSs, targeted distribution, and tumor hypoxia 16 - 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, light source, PSs and O 2 are the three necessary components of PDT. With the continuous development of PSs and optical fiber-guided laser transmission systems, PDT has evolved from theoretical research to clinical research and expanded to imaging and treatment of various cancer and non-cancer diseases 11 - 15 . However, like other therapies, the breadth and depth of PDT's efficacy have not been fully realized due to the limitations such as light penetration depth, inefficient PSs, targeted distribution, and tumor hypoxia 16 - 20 .…”
Section: Introductionmentioning
confidence: 99%
“…And studies have shown that ALA is an extremely powerful drug for PDT [ 24 26 ]. In the heme biosynthesis pathway, ALA is a natural precursor of protoporphyrin IX (PpIX), a commonly used photosensitizer in clinical PDT [ 27 ]. Abundant mitochondria are necessary for the conversion of ALA to PpIX.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells modify their iron metabolism to maximize absorption and minimize outflow, increasing labile iron ( Duan et al, 2019 ). The abnormal metabolism and proliferation of cancer cells require a high level of iron and, consequently, tumor tissues contain a higher amount of iron than normal tissues ( Xu et al, 2020 ). There is also evidence that an abnormal iron metabolism may lead to tumor initiation, proliferation, and metastasis ( Raggi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%